Greeneration: An Innovative Learning Resource for Students' Environmental Awareness - Wijayanto, Bayu; Nurwahdah; Nurazizah, Septina; Laila Tamin, Aulia; Budi Hermawan, Aditya; Utari, Shita; Adawiyah, Jamiatul; Khairul Azim, Muhammad (SOSEARCH : Social Science Educational Research, 2025)
Environmental issues such as pollution, deforestation, and climate change are increasingly worsening. However, students' awareness and concern for the environment remain relatively low. Many students lack an understanding of the impact of human activities on nature, as learning is often theoretical and fails to connect environmental concepts with real-life experiences. Greeneration, as an innovative learning approach, utilizes the environment as a learning resource that provides students with direct experiences. This study aims to explore the impact of using Greeneration as a learning resource on students' environmental awareness, with the hope of offering relevant solutions in the current educational context. The research employs a quantitative approach with an experimental design, involving students from Kuntum Cemerlang High School in Bandung City. Data collection was conducted through a questionnaire designed to measure changes in students' attitudes before and after the intervention. The findings indicate that the implementation of Greeneration significantly enhances students' environmental awareness and concern, with an average increase of 30% in environmental attitude scores after the intervention. These results are expected to contribute to the development of a more environmentally responsive curriculum and encourage the implementation of innovative learning methods that inspire students to take an active role in environmental preservation.